Analysis of the Effect of E-Service on Repurchase Intention with E-Trust and E-Satisfaction as Mediation Variables on Batik Kulon Progo SME Customers - Harwidyasto, Raditya; Sugandini, Dyah; Ambarwati, Sri Dwi Ari (Journal of Business Innovation and Research, 2024)
This research aims to determine the effect of e-service on repurchase intention with e-trust and e-satisfaction as mediating variables for SME Batik customers in Kulon Progo Yogyakarta. The type of research carried out was survey research with a total of 100 respondents. The criteria used in selecting respondents were that they had made online purchases from Batik UKMs in Kulon Progo, the purchases were made during the pandemic or after the pandemic and were at least 17 years old. This research was carried out with the help of SmartPLS 3.2.8 software. And the results obtained in this research are that E-service has a significant effect on repurchase intention in Batik SMEs in Kulon Progo; E-service has a significant effect on e-trust in Batik SMEs in Kulon Progo; E-service has a significant effect on e-satisfaction in Batik SMEs in Kulon Progo; E-service has a significant effect on repurchase intention through e-trust in Batik SMEs in Kulon Progo; and E-service has a significant effect on repurchase intention through e-satisfaction in Batik SMEs in Kulon Progo.